Zur Kenntnis von Strongylogaster xanthoceros (Steph.) und Strongylogaster lineata (Christ) und ihrer Parasiten (Hymenoptera: Tenthredinidae & Ichneumonidae; Diptera: Larvaevoridae). - Welke, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1959)
There are described the genital morphology of the adults, the morphology of the eggs, the five larval instars, and the pupa of Strongylogaster xanthoceros (Steph.) and Strongylogaster lineata (Christ) (Hymenoptera: Tenthredinidae). The life-history of the two species was studied by breeding the two species in the laboratory as like as by field investigations.Among the Ichneumon flies parasitizing Strongylogaster Cubocephalus anatorius (Grav.), Cubocephalus distinctor (Thbg.), and Alexeter niger (Grav.) were bred from the egg. Their hitherto unknown morphology (egg, larval instars, pupa) and bionomy are described. Blondelia nigripes (Fall.) and Bessa selecta (Meig.) are reported as Dipterous parasites of Strongylogaster. There are given notes on the life-history of these two species.